Not One More Time: Navit Barel Reads Shimon Adaf - Barel, Navit (MiKAN, 2021)
A few thoughts about the double movement of memory, both fluent and fragmentary at the same time, in Adafs memorial collection Aviva-No. Barel reads one section of the collection and offers a path to the importance of the mother figure in the mourning process, as the line "to lose a child means to always lose a child" unfolds the trapped being of the mournful self.